Regulatory effects and mechanisms of HOTAIRM1 in malignant tumors - ZHAO Yu-qiao, SU Zhi-lei, CUI Yun-fu, GUAN Cang-hai, JIANG Xing-ming (Jichu yixue yu linchuang, 2021)
HOTAIRM1, a newly found long non-coding RNA (lncRNA), is abnormally expressed in diverse malignant tumors, regulated mRNA, miRNA, relevant target gene or protein through specific signal transduction pathways to function in mechanisms of proliferation, invasion and metastasis of tumor cells. HOTAIRM1 is closely related to the clinicopathology or molecular pathology and have shown great potential in therapy and predicting prognosis of patients.